2009
DOI: 10.1007/s11149-009-9097-0
|View full text |Cite
|
Sign up to set email alerts
|

Does yardstick regulation really work? Empirical evidence from Japan’s rail industry

Abstract: Yardstick regulation, Incentive regulation, Efficiency, Cost frontier function, L51, L53, L90, K23,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…Some studies analyze the cost efficiency change due to regulatory reform, one form of governmental intervention, by using the stochastic cost frontier function (e.g. Kleit and Tecrell 2001;Mizutani et al 2009). Also, theoretical studies have been done which construct the relationship between governmental intervention and the costs of a firm (e.g.…”
Section: Regulation As Governmental Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies analyze the cost efficiency change due to regulatory reform, one form of governmental intervention, by using the stochastic cost frontier function (e.g. Kleit and Tecrell 2001;Mizutani et al 2009). Also, theoretical studies have been done which construct the relationship between governmental intervention and the costs of a firm (e.g.…”
Section: Regulation As Governmental Interventionmentioning
confidence: 99%
“…Nowell and Shogren 1994), incentive regulation (e.g. Berg and Jeong 1991;Vogelsang 2002;Mizutani et al 2009;Ter-Martirosyan and Kwoka 2010), and price regulation (e.g. Cabral and Riordan 1989;Bös and Peters 1995;Vogelsang 2002), or focusing on specific industries: the energy industry (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yardstick regulation with multiple regression analysis was implemented for fifteen large private railway companies, six JRs and ten subways in 1997, while it was not applied to small private railway companies. Mizutani et al (2009) estimated the variable frontier cost function by using data set of large and small private railway companies. They found that large railways to which the yardstick regulation was applied could have improved cost efficiency by 11.5% between 1995 and 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Analizirajući efekte komparativne regulacije Mizutani i ostali [15] su pronašli da su, u Japanu u periodu od 1995. do 2000. godine, železnice na kojima je primenjen ovakav oblike regulacije povećale svoju troškovnu efikasnost za oko 11,5%.…”
unclassified